1993
DOI: 10.1242/jcs.1993.supplement_17.25
|View full text |Cite
|
Sign up to set email alerts
|

Apical junctions and cell signalling in epithelia

Abstract: Genetic analysis in Drosophila has led to the identifica tion of several proteins that mediate cell-cell interactions controlling the fate and proliferation of epithelial cells. These proteins are localized or enriched in the adherens and septate junctions at the apical end of the lateral membranes between cells. The proteins localized or enriched at adherens junctions include Notch, which is important for the cell interactions controlling neuro blast and bristle patterning; Boss and sevenless, which are requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 102 publications
4
53
0
Order By: Relevance
“…Consistent with earlier studies in vertebrate and insect epithelia, we' found that in embryos PY epitopes were localized to the electron-dense cytoplasmic plaques of the ZA ( Fig. 1) (Takata and Singer, 1988;Tsukita et al, 1991, Woods andBryant, 1993). Optical sections through stained wild-type embryos of different stages revealed that Arm and PY colocalize to a large extent (Fig.…”
Section: Formation Of the Za And Basolateral Membrane Identity In Thesupporting
confidence: 90%
“…Consistent with earlier studies in vertebrate and insect epithelia, we' found that in embryos PY epitopes were localized to the electron-dense cytoplasmic plaques of the ZA ( Fig. 1) (Takata and Singer, 1988;Tsukita et al, 1991, Woods andBryant, 1993). Optical sections through stained wild-type embryos of different stages revealed that Arm and PY colocalize to a large extent (Fig.…”
Section: Formation Of the Za And Basolateral Membrane Identity In Thesupporting
confidence: 90%
“…Arthropods, including insects, have septate junctions that are considered to be functional equivalents to tight junctions of vertebrates (47). The tight junction has been shown to be a barrier that prevents materials from going through the intercellular space and maintains cell polarity.…”
Section: Figmentioning
confidence: 99%
“…In ectodermal epithelia of the wild-type embryo, DE-cadherin was restricted to an apical position of cell-cell contacts, and its distribution was segregated from the territory of fasciclin III, a marker for the septate junction, which is located in the subapico-lateral region (Patel et al 1987;Woods and Bryant 1993;see Fig. 2A).…”
Section: De-cadherin Is Encoded By Shotgunmentioning
confidence: 99%